1978
DOI: 10.2307/1938227
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Foraging Behavior of Six Stingless Bee Species Exploiting a Standardized Resource

Abstract: We report on differences in foraging and recruitment patterns among 6 stingless bee species simultaneously exploiting a large grid of baits in a tract of tropical dry forest in Costa Rica. Comparative data for the species were obtained on the following parameters of foraging: time to initial bait discovery, rate of discovery of additional baits, rate of worker recruitment, time till attainment of approximate steady—state number of workers and visited baits, frequency of number of workers per bait, degree of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
103
0
2

Year Published

1986
1986
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 4 publications
7
103
0
2
Order By: Relevance
“…The remarkably precise localization of a food source in scent path laying stingless bees, as shown by several authors (Lindauer andKerr, 1958, 1960;Kerr et al, 1963;Hubbel and Johnson, 1978) and confirmed by our present work, seems to contrast with less precise localization of food sources in non-scent path laying bees of the genus Melipona (Lindauer andKerr, 1958, 1960;Kerr et al, 1963;Nieh and Roubik, 1995;Nieh and Roubik, 1998;Jarau et al, 2000). In Melipona sp.…”
Section: Ecology Of Foraging Strategiessupporting
confidence: 81%
See 1 more Smart Citation
“…The remarkably precise localization of a food source in scent path laying stingless bees, as shown by several authors (Lindauer andKerr, 1958, 1960;Kerr et al, 1963;Hubbel and Johnson, 1978) and confirmed by our present work, seems to contrast with less precise localization of food sources in non-scent path laying bees of the genus Melipona (Lindauer andKerr, 1958, 1960;Kerr et al, 1963;Nieh and Roubik, 1995;Nieh and Roubik, 1998;Jarau et al, 2000). In Melipona sp.…”
Section: Ecology Of Foraging Strategiessupporting
confidence: 81%
“…In the latter case the precision of the recruitment system is highly important for the colony's food acquisition (Visscher and Seeley, 1982;Seeley and Visscher, 1988;Seeley et al 1991, Waddington et al, 1994. Scent trail laying stingless bees, on the other hand, seem to be particularly good at the exact localization of a food source and its exploitation until it is depleted (Hubbel and Johnson, 1978). Furthermore, scent trail recruitment facilitates group foraging, which enables bees to monopolize dense patches of highly rewarding resources with sufficient food for many bees (Johnson and Hubbel, 1975;Hassel and Southwood, 1978;Hubbel and Johnson, 1978).…”
Section: Ecology Of Foraging Strategiesmentioning
confidence: 99%
“…Such a prolonged reluctance to land seems unlikely given that food competition among stingless bees is intense and time critical. The availability of food sources, not nest sites, appears to limit the density of stingless bee species, and the competition for these resources is usually won by the colony that can most rapidly recruit a large number of foragers (Johnson and Hubbell 1974;Hubbell and Johnson 1978). In the removal experiments testing the communication of distance inside the nest, could more newcomers have arrived at the training feeder because it was located at the same distance as natural food sources?…”
Section: Discussionmentioning
confidence: 99%
“…The immediate needs of the colony, internal conditions such as the quantity of pollen, honey or resin stored and reproductive phases may further define what resources are collected and to what intensity. Competition for floral resources by coexisting highly eusocial species was thought to play a major role in determining foraging behaviour patterns in Meliponini (HUBBELL & JOHNSON 1977, 1978, ROUBIK 1980. ROUBIK (1989) emphasises that bee foraging patterns are determined both by extrinsic and intrinsic variables that vary among species.…”
mentioning
confidence: 99%